Antecedents and Impacts of Digital Customer Experience in Youth E-Commerce Engagement - Zulfahmi Zulfahmi; Hubertina Karolina Ngarbingan; Ginta Ginting; Maya Maria (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2026)
To analyze the antecedents and implications of digital customer experience. The proposed research model integrates several theories and approaches, namely 1) Information Integration Theory (IIT), 2) Multi Attribute Theory (MAUT), 3) Value Co-Creation Theory, 4) Theory of flow. From the integration of these theories and concepts, the variables used in the modeling are: online flow, value co-creation, digital customer experience, and customer loyalty. This study involved 182 respondents  (young people aged 17 to 45), living in Jakarta and its surrounding cities. Data were processed using Smart-PLS to determine the relationships between variables. The results show that online flow state significantly influences value co-creation, and value co-creation influences digital customer experience. An interesting finding from this research is that digital customer experience and online flow state can be proven to significantly influence customer loyalty. The hypothesis test examines the indirect effect of online flow state on customer loyalty through two consecutive mediators: value co-creation and digital customer experience. The results indicate a significant double mediation effect. To achieve customer loyalty in the context of e-commerce, companies need to strategically create engaging online experiences (trigger flow), encourage active customer participation in value creation, and ultimately, ensure that all of this results in a superior digital customer experience. Based on the research findings, the following recommendations are: a) Prioritize Experience Design that Inspires "Flow": invest more in immersive, intuitive, and seamless user interface/user experience design. Use gamification elements, intelligent personalization, and responsive interactions to minimize distractions and maximize user engagement., b)  Facilitate and Reward Value Co-Creation: create and optimize platforms that enable active customer participation. This could take the form of an active community forum, an easily accessible and rewarded product review system, a publicly accessible "wishlist" or "product idea" feature, or even a limited co-design program for new products or features. Ensure customer contributions are visible and valued., c) 1) Improve the Quality of the Digital Customer Experience Comprehensively: Companies must continuously audit and improve every digital touchpoint. This includes page load speed, design responsiveness across devices, digital customer service efficiency (AI chatbots, live chat), transaction security, and branding consistency across platforms.